Apelin-13 regulates angiotensin ii-induced Cx43 downregulation and autophagy via the AMPK/mTOR signaling pathway in HL-1 cells - Chen, Y; Qiao, X; Zhang, L; Li, X; Liu, Q (Physiological research, 2020)
Atrial fibrillation is associated with atrial remodeling, in which connexin 43 (Cx43) and cell hypertrophy play important roles. In this study, apelin-13, an aliphatic peptide, was used to explore the protective effects of the adenosine monophosphate-activated protein kinase (AMPK)/mTOR signaling pathway on Cx43 expression and autophagy, using murine atrial HL-1 cells. The expression of Cx43, AMPK, B-type natriuretic peptide (BNP) and pathway-related proteins was detected by Western blot analysis. Cellular fluorescence imaging was used to visualize Cx43 distribution and the cytoskeleton. Our results showed that the Cx43 expression was significantly decreased in HL-1 cells treated with angiotensin II but increased in cells additionally treated with apelin-13. Meanwhile, apelin-13 decreased BNP expression and increased AMPK expression. However, the expression of Cx43 and LC3 increased by apelin-13 was inhibited by treatment with compound C, an AMPK inhibitor. In addition, rapamycin, an mTOR inhibitor, promoted the development of autophagy, further inhibited the protective effect on Cx43 expression and increased cell hypertrophy. Thus, apelin-13 enhances Cx43 expression and autophagy via the AMPK/mTOR signaling pathway, and serving as a potential therapeutic target for atrial fibrillation.
Keywords: TOR Serine-Threonine Kinases; signální transdukce; Signal Transduction; Connexin 43; konexin 43; lékové interakce; Down-Regulation; TOR serin-threoninkinasy; kardiomyocyty; Angiotensin II; angiotensin II; proteinkinasy aktivované AMP; Atrial Fibrillation; zvířata; autofagie; myši; Intercellular Signaling Peptides and Proteins; Myocytes, Cardiac; down regulace; Vasoconstrictor Agents; AMP-Activated Protein Kinases; Mice; buněčné linie; Drug Interactions; Cell Line; mezibuněčné signální peptidy a proteiny; vazokonstriktory; Animals; Autophagy; fibrilace síní